2019
DOI: 10.3390/coatings9080479
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Ammonium Thiocyanate-Modified Geopolymeric Coating for Flame-Retarding Plywood

Abstract: An ecological ammonium thiocyanate (NH4SCN)-modified geopolymeric coating was facilely prepared for flame-retarding plywood. The effect of NH4SCN on the flame resistance was preliminarily investigated using cone calorimeter (CC), scanning electron microscope (SEM), X-ray diffraction (XRD), and thermal gravimetry (TG). The results show that 1 wt.% NH4SCN as dopant is of paramount importance to generate a compact and continuous coating. The formation of a smooth, intact, and uniform-swelling siliceous layer duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The combustion process of wood may be divided into drying, pre-carbonization, carbonization and combustion, and the HRR depends on the structural stability of the wood component. In all diagrams, a first peak appears at <50 s, assigned to the decomposition of light volatile and partial hemicellulose, and a second peak appears at ~300-350 s, attributed to the remaining hemicellulose, cellulose and partial lignin, which are the stages of the sequential decomposition of wood [38].…”
Section: Fire Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combustion process of wood may be divided into drying, pre-carbonization, carbonization and combustion, and the HRR depends on the structural stability of the wood component. In all diagrams, a first peak appears at <50 s, assigned to the decomposition of light volatile and partial hemicellulose, and a second peak appears at ~300-350 s, attributed to the remaining hemicellulose, cellulose and partial lignin, which are the stages of the sequential decomposition of wood [38].…”
Section: Fire Test Resultsmentioning
confidence: 99%
“…Suihkonen et al [55] observed a significant decrease (71%) in the burning rate of samples EP-10-N and EP-10-NU as a function of magnesium hydroxide (MDH) content compared to neat epoxy, indicating an improvement in flame-retardant properties upon MDH addition. Wang et al [38] prepared ammonium thiocyanate (NH 4 SCN)-modified geopolymeric coatings and observed delayed flame propagation with the increasing content of NH 4 SCN up to 1 wt.%, since exceeding this dosage had a detrimental effect on flame retardancy.…”
Section: Fire Test Resultsmentioning
confidence: 99%